Characteristics Of Hydrothermal Alteration In Cijulang Area, West Java, Indonesia - Myo Min Tun; I Wayan Warmada; Agung Harijoko; Reza Al-Furqan; Koichiro Watanabe (Geological Engineering Department Universitas Gadjah Mada, 2015)
Characterization of hydrothermal alteration in theCijulang area (West Java, Indonesia) was carriedout using shortwave infrared spectroscopy. Hydrothermal alteration in the Cijulang area occurs in the calc-alkaline volcanic and volcaniclastic rocks. Shortwave infrared spectroscopic measurements of reflectance for altered rocks and minerals were carried out by ASD-FieldSpec and the laboratory spectra acquired were then analysed with “The Spectral Geologist” software program. Shortwave infrared spectroscopy is capable of detecting most finegrained alteration minerals from different hydrothermal alteration zones. Characteristic alteration minerals identified from the SWIR technique include pyrophyllite, alunite, kaolinite, dickite, illite, montmorillonite, polygorskite, gypsum, epidote, paragonite, and muscovite. Most of the spectra show mixture ofalteration minerals and only a few display pure spectra of single mineral. The crystallinity of kaolinite from the samples was also determined from the reflectance spectra and show moderately to high crystallinity. Alteration system of the Cijulang prospectis similar to others documented high-sulfidation epithermal deposits, such as Rodalquilar (Spain), Summitville (Colorado), and Lepanto (Philippines). A characteristic alteration sequence and zonation of advanced argillic, argillic and propylitic alterationoutward from the silica core has resulted from the progressive cooling and neutralization of hot acidic magmatic fluid with the host rocks.Keywords: Cijulang, High-sulfidation, Alteration minerals, Shortwave Infrared Spectroscopy